RAGAM GENETIK KANDUNGAN ASAM LEMAK, BILANGAN IODINE DAN BETA KAROTEN 24 AKSESI PLASMA NUTFAH KAMERUN KOLEKSI PUSAT PENELITIAN KELAPA SAWIT - Sujadi Sujadi; Hasrul Abdi Hasibuan; Abdul Razak Purba; Mahmud Irvan Lubis (Jurnal Penelitian Kelapa Sawit, 2017)
Twenty four Cameroon accessions have been planted in Adolina oil palm seed garden area in 2010 and have been analyzed their fatty acid, iodine value and beta carotene contents to reveal their genetic variability. Analysis of variance results for fatty acid, iodine value and beta carotene content characters show that there are significant differences for palmitat, stearat, oleat, linoleat acid, iodine value and beta carotene content. Fatty acid content, iodine value and beta carotene content showed medium to high broad sense variability which verify that there is a high genetic impact of these characters. Ten Cameroon accessions with beta carotene content more than 1.000 ppm have been identified and can be used as future breeding material for IOPRI in gaining new varieties with beta carotene content more than 1.000 ppm. In addition there is one accession showed iodine value more than 57.1 Wijs which has a potential used as crossing material in obtaining new superior varieties which have high iodine values. In outline there are negative correlation( in one side) between palmitat acid with stearat, oleat acid and iodine value in other side.